Right to Education - Krunková, Alena (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
As one of the fundamental rights and freedoms, the right to education belongs to the second generation of human rights. It is crucial not only for the development of personality, but also for societal progress. Even in the twenty-first century, judicial protection remains necessary, as its implementation cannot be taken for granted. The first section of this paper considers the definition of the right to education as it has gradually evolved on the European continent. We highlight its key characteristics and distinctive features and specify its position within major international documents on the protection of human rights. The second section addresses the case law of the European Court of Human Rights in relation to the right to education under the Convention for the Protection of Human Rights and Fundamental Freedoms. Cases of its violation, either freestanding or in interaction with other fundamental human rights, are analysed casuistically. Keywords: Right to education, Convention for the Protection of Human Rights and Fundamental Freedoms, European Court of Human Rights, case law